Respiratory modulation of human autonomic function: long‐term neuroplasticity in space. (26th July 2016) - Eckberg, Dwain L.; Diedrich, André; Cooke, William H.; Biaggioni, Italo; Buckey, Jay C.; Pawelczyk, James A.; Ertl, Andrew C.; Cox, James F.; Kuusela, Tom A.; Tahvanainen, Kari U.O.; Mano, Tadaaki; Iwase, Satoshi; et al.
Abstract : Key points: We studied healthy astronauts before, during and after the Neurolab Space Shuttle mission with controlled breathing and apnoea, to identify autonomic changes that might contribute to postflight orthostatic intolerance. Measurements included the electrocardiogram, finger photoplethysmographic arterial pressure, respiratory carbon dioxide levels, tidal volume and peroneal nerve muscle sympathetic activity. Arterial pressure fell and then rose in space, and drifted back to preflight levels after return to Earth. Vagal metrics changed in opposite directions: vagal baroreflex gain and two indices of vagal fluctuations rose and then fell in space, and descended to preflight levels upon return to Earth. Sympathetic burst frequencies (but not areas) were greater than preflight in space and on landing day, and astronauts' abilities to modulate both burst areas and frequencies during apnoea were sharply diminished. Spaceflight triggers long‐term neuroplastic changes reflected by reciptocal sympathetic and vagal motoneurone responsiveness to breathing changes. Abstract: We studied six healthy astronauts five times, on Earth, in space on the first and 12th or 13th day of the 16 day Neurolab Space Shuttle mission, on landing day, and 5–6 days later. Astronauts followed a fixed protocol comprising controlled and random frequency breathing and apnoea, conceived to perturb their autonomic function and identify changes, if any, provoked by microgravity exposure. We recorded the electrocardiogram, finger photoplethysmographic arterial pressure, tidal carbon dioxide concentrations and volumes, and peroneal nerve muscle sympathetic activity on Earth (in the supine position) and in space. (Sympathetic nerve recordings were made during three sessions: preflight, late mission and landing day.) Arterial pressure changed systematically from preflight levels: pressure fell during early microgravity exposure, rose as microgravity exposure continued, and drifted back to preflight levels after return to Earth. Vagal metrics changed in opposite directions: vagal baroreflex gain and two indices of vagal fluctuations (root mean square of successive normal R‐R intervals; and proportion of successive normal R‐R intervals greater than 50 ms, divided by the total number of normal R‐R intervals) rose significantly during early microgravity exposure, fell as microgravity exposure continued, and descended to preflight levels upon return to Earth. Sympathetic mechanisms also changed. Burst frequencies (but not areas) during fixed frequency breathing were greater than preflight in space and on landing day, but their control during apnoea was sharply altered: astronauts increased their burst frequencies from already high levels, but they could not modulate either burst areas or frequencies appropriately. Space travel provokes long‐lasting sympathetic and vagal neuroplastic changes in healthy humans. Key points: We studied healthy astronauts before, during and after the Neurolab Space Shuttle mission with controlled breathing and apnoea, to identify autonomic changes that might contribute to postflight orthostatic intolerance. Measurements included the electrocardiogram, finger photoplethysmographic arterial pressure, respiratory carbon dioxide levels, tidal volume and peroneal nerve muscle sympathetic activity. Arterial pressure fell and then rose in space, and drifted back to preflight levels after return to Earth. Vagal metrics changed in opposite directions: vagal baroreflex gain and two indices of vagal fluctuations rose and then fell in space, and descended to preflight levels upon return to Earth. Sympathetic burst frequencies (but not areas) were greater than preflight in space and on landing day, and astronauts' abilities to modulate both burst areas and frequencies during apnoea were sharply diminished. Spaceflight triggers long‐term neuroplastic changes reflected by reciptocal sympathetic and vagal motoneurone responsiveness to breathing changes.